Fetal MRI of the heart and brain in congenital heart disease. (January 2023) - Moerdijk, Anouk S; Claessens, Nathalie HP; van Ooijen, Inge M; van Ooij, Pim; Alderliesten, Thomas; Grotenhuis, Heynric B; ,; Bekker, MN; Benders, MJNL; Bohte, AE; Breur, JMPJ; Charisopoulou, D; et al.
Summary: Antenatal assessment of congenital heart disease and associated anomalies by ultrasound has improved perinatal care. Fetal cardiovascular MRI and fetal brain MRI are rapidly evolving for fetal diagnostic testing of congenital heart disease. We give an overview on the use of fetal cardiovascular MRI and fetal brain MRI in congenital heart disease, focusing on the current applications and diagnostic yield of structural and functional imaging during pregnancy. Fetal cardiovascular MRI in congenital heart disease is a promising supplementary imaging method to echocardiography for the diagnosis of antenatal congenital heart disease in weeks 30–40 of pregnancy. Concomitant fetal brain MRI is superior to brain ultrasound to show the complex relationship between fetal haemodynamics in congenital heart disease and brain development.